Modelo baseado em processamento de dados heterogêneos para aplicações de apoio clínico - Rönnau, Rodrigo Freiberger (Universidade do Vale do Rio dos Sinos, 2017)
The use of computer systems to aid in the clinical practice has been widely studied, seeking an evaluation of its possibilities in improving the quality of the care provided to patients. Among the applications for this purpose, it is possible to highlight those that act on medical reports or medical images, in activities that perform the extraction, storage and use of characteristics acquired through the processing of these documents. However, observing the literature of the area, it is noticed that there is a gap in the combined use of information obtained in each type of processing, while indicating, at the same time, relevant possibilities of applications sharing and integrating this information. Another identified gap is related to the interoperability of the data and results obtained between different existing systems. In order to contribute to the solution of the presented questions, this work proposes a model, with a modular and expandable structure, which makes possible the use of different input formats with the objective of providing, in an integrated way, support information to the physician or specialist. The extracted data are made available in a structured manner through recognized standards, allowing the interoperability between the systems and their use from different computational applications. Two prototypes were constructed, using as basis the proposed model. Scenarios that demonstrate the use and benefits of the model have been described and used in its evaluation. Both the model and the prototypes were presented to 12 health professionals and 35 computer professionals. Participants completed an evaluation questionnaire. As result, 97.8% of respondents indicated that the proposed model is useful and 76.6% intend to use it and/or disseminate it.
Keywords: Informática médica; Dados heterogêneos; Processamento de imagens; Processamento de linguagem natural; Medical informatics; Heterogeneous data; Image processing; Natural language processing; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação